Does Active Labour Market Policy Work? Lessons from the Swedish Experiences - Lars Calmfors; Anders Forslund; Maria Hemström (Center for Economic Studies and ifo Institute (CESifo), 2002)
The Swedish experiences of the 1990s provide a unique example of how large-scale active labour market programmes (ALMPs) have been used as a means to fight high unemployment. This paper surveys the empirical studies of the effects of ALMPs in Sweden. On the whole, ALMPs have probably reduced open unemployment, but also reduced regular employment. The overall policy conclusion is that ALMPs of the scale used in Sweden in the 1990s are not an efficient means of employment policy. To be effective, ALMPs should be used on a smaller scale.
Keywords: 330